2020
DOI: 10.1136/jitc-2020-000710
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic vaccinia virus delivering tethered IL-12 enhances antitumor effects with improved safety

Abstract: Immune checkpoint blockade is arguably the most effective current cancer therapy approach; however, its efficacy is limited to patients with “hot” tumors, warranting an effective approach to transform “cold” tumors. Oncolytic viruses (especially properly armed ones) have positive effects on almost every aspect of the cancer–immunity cycle and can change the cancer–immune set point of a tumor. Here, we tested whether oncolytic vaccinia virus delivering tethered interleukin 12 (IL-12) could turn a “cold” tumor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 30 publications
0
47
0
2
Order By: Relevance
“…In this regard, combining PD‐1 blockade with SIRPα‐Fc seems particular promising based on the recent finding that TAMs express high levels of PD‐1 57 . In addition, inserting cytokine genes such as IL‐12 or IL‐15 could change the immunosuppressive tumor microenvironment into a pro‐inflammatory environment bolstering the effect of SIRPα‐Fc 58,59 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, combining PD‐1 blockade with SIRPα‐Fc seems particular promising based on the recent finding that TAMs express high levels of PD‐1 57 . In addition, inserting cytokine genes such as IL‐12 or IL‐15 could change the immunosuppressive tumor microenvironment into a pro‐inflammatory environment bolstering the effect of SIRPα‐Fc 58,59 …”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, studies that augment the OV's function via cytokine and chemokine coexpression have been reported. Ge et al 40 showed that OV delivering tethered IL-12 was able to avoid systemic toxicity and cure all mice with late-stage colon cancer, by facilitating T-cell infiltration, increasing IFN-c and decreasing suppressive factor TGF-b in the tumor.…”
Section: Oncolytic Viruses/bacteriamentioning
confidence: 99%
“…Consequently, the IL-12-armed oncolytic HSV-1 resulted in better survival compared to the unarmed virus. Ge et al studied the safety and antitumor efficacy of an oncolytic vaccinia virus encoding a membrane-bound version of IL-12 [61]. The virus was found to convert an immunologically "cold" tumor into a "hot" one, and to increase the survival of mice bearing syngeneic colon tumors.…”
Section: Interleukin-12mentioning
confidence: 99%